What should be added to 1+2x-3x to get x-x-1?
Answers
Answered by
2
Answer:
Given;
What should be added to 1+2x-3x^{2}1+2x−3x
2
to get x^{2} -x-1x
2
−x−1
Let,
If we add aa with 1+2x-3x^{2}1+2x−3x
2
then get x^{2} -x-1x
2
−x−1
∴a+1+2x-3x^{2}=x^{2} -x-1a+1+2x−3x
2
=x
2
−x−1
⇒a=x^{2} -x-1-1-2x+3x^{2}a=x
2
−x−1−1−2x+3x
2
⇒a=4x^{2} -3x-2a=4x
2
−3x−2
∴ If we add 4x^{2} -3x-24x
2
−3x−2 with 1+2x-3x^{2}1+2x−3x
2
then get x^{2} -x-1x
2
−x−1
Answered by
0
Step-by-step explanation:
This is the correct answer which is above mentioned
Attachments:
![](https://hi-static.z-dn.net/files/d58/e175f468754288ce34329a27f87a5079.jpg)
Similar questions